Social representations and food neophobia of vegetarian ready-to-eat meals cooked by sous-vide - Aviles, Maria Victoria (2024)
This study aimed to analyze the frequency of orange-fleshed sweet potato and pumpkin consumption, the social representations of sous-vide cooked vegetarian ready-to-eat meals (vegetable millefeuille, vegetable mix, and sweet potato provencal), and the correlation between the three meals mentioned, food neophobia, and willingness to buy and try. The study involved 1034 individuals aged 18 and above from Argentina. A Correspondence Analysis was performed to visualize the attributes of three stimuli evaluated through word association. The results reflect a high frequency of words related to hedonic terms. A positive correlation between the participants´ levels of food neophobia and their willingness to buy and try each product was found. Participants with lower levels of neophobia showed a greater intention to consume and purchase the vegetable millefeuille and the vegetable mix. Participants with higher neophobia scores demonstrated less willingness to buy sweet potatoes provencal. Using pumpkin and sweet potato as ingredients of prepared dishes presents an opportunity to increase the demand and added value of widely available vegetables that are part of the world gastronomy industry.